Transpot (Tanaman Sayuran Dalam Pot) Solusi Optimalisasi Pekaranhan Sempit Untuk Meningkatkan Ketahanan Pangan Dan Ekonomi Keluarga - Cut Gustiana; Dyah Ayu Ardiyanti; Silvia Anzitha; Thursina Mahyuddin (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2023)
TRANSPOT cultivation is the cultivation of vegetable plants in pots, which because it has several advantages including the use of narrow yards or yards, serves as a provision for vegetable plants, is easy to move without damaging the plants and can adjust the harvest period. TRANSPOT (Planting Vegetables in Pots) is one of the solutions for optimizing narrow yards to increase food security and the family economy carried out in Gampong Baroh Langsa Lama, located in Langsa Lama District. Service partners are housewives in Baroh Langsa Lama village/gampong. One of the partner's problems is the lack of partner skills and knowledge in utilizing the yard. By equipping partners with the skills to use the yard, they will be able to bring benefits, besides meeting the family's food needs, they are also able to increase family income. Growing vegetable plants in sustainable pots includes the use of narrow yards to become creative and innovative TRANSPOTs, such as taboo lampot vegetables, taboo lampot fruits, and green environmental innovations. This activity of planting vegetables using pot media has a positive impact on the availability of independent food for each family, besides that this activity can also be a source of family economic income and assist the government in providing healthy food sources for the community. Vegetable plants in pots are expected to be a solution to increase the community's economy